The Position Of Regional Notary Honorary Council In Providing The Approval Toward The Notary Audit In The Investigation Process - Nurhasaniah Nurhasaniah; Rizanizarli Rizanizarli; Suhaimi Suhaimi (Universitas Islam Negeri Antasari Banjarmasin, 2022)
Abstrak: Notaris mempunyai kewajiban untuk menjaga kerahasian terkait akta yang dibuatnya, oleh karenanya UUJN memberikan perlindungan terhadap Notaris melalui Pasal 66 yang menentukan bahwa untuk kepentingan Penyidikan, Penuntut Umum dan Hakim dengan persetujuan MKN dapat mengambil fotokopi Minuta Akta dan/atau surat-surat yang dilekatkan pada Minuta Akta atau Protokol Notaris dalam penyimpanan Notaris dan memanggil Notaris untuk hadir dalam pemeriksaan yang berkaitan dengan Akta atau Protokol Notaris yang berada dalam penyimpanan Notaris. Penelitian ini bertujuan untuk mengetahui serta menjelaskan tentang kedudukan MKNW dalam sistem hukum Indonesia dalam memberikan surat persetujuan terhadap pemeriksaan Notaris dalam proses Penyidikan. Jenis penelitian yang digunakan adalah yuridis normatif dengan pendekatan undang-undang, pendekatan konseptual dan pendekatan sejarah. Hasil penelitian ini adalah bahwa MKNW memenuhi unsur-unsur sebagai Badan/Pejabat Tata Usaha Negara yang diatur dalam UU PTUN dan UU Administrasi Pemerintahan. MKNW menjalankan urusan pemerintahan berdasarkan UUJN. Selainjutnya Surat persetujuan MKNW terhadap pemeriksaan Notaris dalam proses Penyidikan juga memenuhi unsur-unsur sebagai Surat Keputusan Badan/Pejabat Tata Usaha Negara yang diatur dalam UU PTUN dan UU Adminitrasi Pemerintahan.Kata Kunci: Majelis Kehormatan Notaris Wilayah, kedudukan MKNW, Pengadilan Tata Usaha Negara, Notaris, Penyidikan. Abstract: Notaries should maintain the confidentiality of the deed and the Notary Protocol that is to be stored based on the provisions of the Law on Notarial Position (UUJN) and the Notary Position Code of Ethics. In essence, the UUJN protects Notaries through Article 66 of the UUJN which stipulates that for the investigation, the Public Prosecutor and Judge with the approval of the Notary Honorary Council (MKN) can have a copy of the Minutes of Deed and/or letters attached to the Minutes of Deed or the Notary Protocol in the Notary's storage. Additionally, it also can summon the Notary to be present in the inspection related to the Notary Deed or Protocol that is in the Notary's storage. This study aims to explain the position of the Regional Notary Honorary Council (MKNW) in the Indonesian legal system related to the MKNW approval letter for the examination of a Notary in the Investigation process. This study also explains the court's Absolute Competence in examining, deciding, and resolving lawsuits against the MKNW approval letter. This research used normative juridical through utilizing the law, conceptual, and historical approaches in conducting the data. The sources of legal materials in the study are secondary data consisting of primary, secondary, and tertiary legal materials. The result of this study indicates that MKNW fulfills the elements as a State Administrative Agency/Officer based on the provisions of the Law on State Administration and the Law on the State Administrative Court. This also shows that the MKNW approval letter for the Notary Examination in the Investigation Process fulfills the elements as a State Administrative Decree. Furthermore, based on the provisions in the Government Administration Law and the State Administrative Court Law, it can be determined that the lawsuit dispute related to the MKNW approval letter against a Notary examination in the Investigation process is the Absolute Competence of the State Administrative Court in order to examine, decide and resolve the disputes. The suggestion derived from this study is the hope that there will be administrative efforts that can be taken by a Notary to resolve the problems related to objections to the MKNW approval letter against a Notary examination in the Investigation process. In addition, it is hoped that the Supreme Court will be able to stipulate the Supreme Court Regulations concerning Guidelines for Judicial Body Dispute Resolution. In this case, the settlement of lawsuits against the MKNW approval letter is the Absolute Competence of the State Administrative Court.Keywords: Regional Notary Honorary Council, MKNW Position, State Administrative Court, Notary, Investigation